OPTIMALISASI PRODUKSI OLEORESIN DARI KULIT ARI BIJI KAKAO (THEOBROMA CACAO L.) DAN PEMANFAATANNYA DALAM PENGOLAHAN PANGAN - Amalia Noviyanty; Mappiratu Mappiratu; Nur Alam (Agroland: Jurnal Ilmu-ilmu Pertanian, 2015)
This research was conducted to produce oleoresin from the cacao bean husk in optimum condition (ratio ethanol/cacao bean husk and timeof extraction) and to utilize it ini food processing as food flavor.  The research was conducted in stages. Stage I was extraction optimalization and production of oleoresin in two treatment, i.e. ethanol/cacao bean husk (v/b) with 8 extents, 5 : 1, 6 : 1, 7 :1, 8 : 1, 9 : 1, 10 : 1, 11 : 1 and 12 : 1 and time of extraction with 4 extents, 1 hour, 2 hour, 3 hour and 4 hour, using Completely Randomized Design applied to the observation of extract yield and total phenolic; stage II was oleoresin application of cacao bean husk in 5 extents, i.e. 2.5%, 5.0%, 7.5%, 10% and 12.5% using Randomized Block Design applied in the observation of organoleptic test.  The research result show that the ratio of ethanol/cacao bean husk 11 : 1 (v/b) and 2 hour extraction time gave the best extract yield i.e. 1.48% and the best total phenolic 0.58%.  Oleoresin concentration of 10% applied to biscuit gave the best effect compared than oleoresin concentration again.       Key words : Cacao bean husk, extract yield, oleoresin production, optimum condition, and total phenolic.